Studies on Activator Formation in Human Plasma with Streptokinase - Martin, M; Technical Assistance; Auel, Miss H (Thrombosis and Haemostasis, 1976)
A new method is presented for estimating the activator (plasminogen-streptokinase complex) concentration in native plasma of patients undergoing streptokinase infusion. The principle of the method is based on clot lysis time as recorded by the thromboelastograph. The test clot constituents were bovine fibrinogen, bovine plasminogen, EDTA, human plasma (with unknown activator concentrations), and thrombin. In order to obtain a standardization line, urokinase dissolved in NaCl solution was substituted for patients’ plasma. Thus, each lysis time could easily be converted into urokinase equivalent (CTA-u/ml). Streptokinase and plasminogen molecules in undiluted patients’ plasma were found to exist both in an activator-bound (equimolar plasminogen-streptokinase complex) and in a freely circulating form. This result is in agreement with earlier findings where the activator complex was demonstrated to be a widely dissociated complex in highly diluted plasma of patients, thus displaying an ample proportion of free streptokinase and plasminogen molecules. Streptokinase treatment using dosage schemes of 100,000 u SK/h, 150,000 u/h, and 200,000 u/h were monitored by quantitative activator, streptokinase, and plasminogen measurements. An average activator concentration of 50–100 CTA-u/ml and a SK-concentration of 7–16 u/ml were recorded during streptokinase infusion. Plasminogen values averaged 0.25%, independent of the amount of streptokinase infused. Each drop in streptokinase was accompanied by a drop in activator during the infusion, and each rise in streptokinase by a rise in activator. There was a strong correlation between streptokinase and activator concentrations in that, on the average, 1 u streptokinase equalled 8.4 CTA-u/ml activator (correlation coefficient r = 0.9). It is concluded that the activator concentration in the plasma of patients undergoing fibrinolytic treatment can easily be adjusted by regulating the hourly streptokinase influx.